Measures of neuropsychological assessment as indicators of success in neuropsychological rehabilitation: an exploratory correlational study - Mendes, Liliana (2021)
Neuropsychological assessment not only allows diagnosing possible neurocognitive impairments in domains such as attention, working memory, and executive functions, but can also provide useful information for the neuropsychological rehabilitation. By applying a set of valid neuropsychological tests to individuals with Acquired Brain Injury (ABI), and subsequently studying how patients’ performance in rehabilitation programs relates with measures that are commonly provided by these tests, we may obtain valuable predictors of individual success that can be considered in neuropsychological rehabilitation.